Development of a questionnaire on awareness and action towards symptoms and risk factors of heart attack and stroke among a Malaysian population - Ahmed, Abdullah Abdulmajid Abdo; Al-Shami, Abdulkareem Mohammed; Jamshed, Shazia Qasim; Nahas, Abdul Rahman Fata (BioMed Central, 2019)
Background The awareness of symptoms and action towards heart attack and stroke is important to reduce the morbidity and mortality in both developed and developing countries. The aim of this study was to develop a questionnaire on awareness and action towards symptoms and risk factors of heart attack and stroke among lay public in Malaysia. The questionnaire was developed in both English and Bahasa Melayu.